DETERMINATION OF FIRM VALUE IN THE REAL ESTATE SECTOR ON THE INDONESIAN STOCK EXCHANGE - Agnes Soukotta; Pandu Adi Cakranegara; Rianda Hanis; Y. Jhony Kurniawan (Jurnal Ekonomi, 2023)
Condition The decline in Indonesia's economic growth is different from the improving condition of the real estate industry. The role of the real estate industry has increased since 2022, growing by 3.02%, supported by increased investment in certain industrial groups. This study aims to determine the internal and external factors that affect the value of real estate companies in Indonesia. Sampling by purposive sampling obtained 19 companies. This study uses multiple linear regression analysis. Found a positive and significant influence between institutional ownership, debt policy and profitability on firm value. But not with dividend policies and interest rates which have no impact on company value. The implication is that investors need to pay attention to the size of institutional ownership which indicates that the company is well managed. In addition, debt and profitability policies also need to be considered by potential investors as investment considerations. Companies that are in debt, the prospects for expanding the company tend to be high, so if they have high profits, they will have good value in the eyes of investors.